2023
DOI: 10.2147/ijgm.s393240
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Motivators to Organ Donation: A Qualitative Exploratory Study in Gujarat, India

Abstract: Purpose Despite the global efforts to improve organ donation, there is a demand-supply gap for organs in India. The only solution to meet this disparity is to improve deceased donor transplants in the country through victims of road accidents. The government has instituted several initiatives to achieve this goal. However, challenges and barriers continue to affect the organ donation process. The present study aims to document the motivating factors and obstacles in the decision of families to don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…[ 24 ] The study by Saxena et al . [ 25 ] in India showed that giving life to a fellow human being and tendency for survival rather than annihilation are among the main reasons for family members’ consent to organ donation from patients who are potential candidates for organ donation. The significant point in this part is the dual role of religious beliefs regarding the consent to organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] The study by Saxena et al . [ 25 ] in India showed that giving life to a fellow human being and tendency for survival rather than annihilation are among the main reasons for family members’ consent to organ donation from patients who are potential candidates for organ donation. The significant point in this part is the dual role of religious beliefs regarding the consent to organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…Different opinions and disagreements between family members can affect the donation process, which is considered one of the main barriers to giving consent [40]. These conflicts may arise due to personal views, beliefs, and attitudes toward organ donation, even if those views do not necessarily reflect the potential donor's wishes or are unknown [41].…”
Section: Discussionmentioning
confidence: 99%